KONSEP TABUNGAN DAN INVESTASI - Raiha Ravitta Putri; Intan Ayu Noverita; Sekar Arumandani; Muhammad Taufiq Abadi (CV. ALIM'SPUBLISHING, 2024)
This research aims to investigate the relationship between savings and investment theory in the concept of economic growth. Savings and investment theory are two main elements in macroeconomi analysis that play an important role in determining the level of economic growth of a country. This research explores the impact of the interaction between savings and investment levels on economie growth. In both conventional and Islamic economic contexts, savings and investments are importan inancial instruments in managing personal finances, supporting economic growth, and achieving the inancial goals of individuals and society as a whole. However, in Islamic economics, both must comply with Sharia principles to create economic justice and religious obedience. reserves of funds that can be used for future consumption or investment. Meanwhile, in Islamic economics, sharia-based savings must comply with sharia principles which prohibit usury and transactions involving haram elements. The goals of savings in Islam include sharia compliance, financial security, and distribution of wealth to the needy.